Coupling of Li motion and structural distortions in olivine LiMnPO4 from 7Li and 31P NMR - Rudisch, Christian; Grafe, Hans-Joachim; Geck, Jochen; Partzsch, Sven; Zimmermann, M. v.; Wizent, Nadja; Klingeler, Rüdiger; Büchner, Bernd (Physical review. B, Condensed matter and materials physics, 2013)
We present a detailed 7Li- and 31P-NMR study on single crystalline LiMnPO4 in the paramagnetic and antiferromagnetic phase (AFM, TN∼34 K). This allows us to determine the spin directions in the field-induced spin-flop phase. In addition, the anisotropic dipolar hyperfine coupling tensor of the 7Li and 31P nuclei is also fully determined by orientation and temperature-dependent NMR experiments and compared to the calculated values from crystal structure data. Deviations of the experimental values from the theoretical ones are discussed in terms of Mn disorder which is induced by Li disorder. In fact, the disorder in the Mn sublattice is directly revealed by diffuse x-ray scattering data. The present results provide experimental evidence for the Li diffusion strongly coupling to structural distortions within the MnPO4 host, which is expected to significantly affect the Li mobility as well as the performance of batteries based on this material.
Im Text ist "7" und "31" hochgestellt, "4" tiefgestellt
Gesehen am 21.01.2022